Late Bronze Age Cultic Activity in Ancient Canaan: A View from Tel Burna - Shai, Yitsḥaḳ (Bulletin of ASOR, 2015)
Excavations at Tel Burna, Israel, have uncovered portions of a large structure from the Late Bronze Age IIB, yielding numerous finds that suggest ritual and cultic practices occurred in the building, particularly in its central courtyard. This article presents the finds from the excavations, examining the meaning of the cultic artifacts discovered and comparing the building with the nearby Fosse Temple at Lachish. It is hoped that the discovery and presentation of the finds will help yield important information on cultic practices occurring in the 13th-century B.C.E. Shephelah.